Piloting positive psychology resources for caregivers of a child with a genetic developmental and epileptic encephalopathy. (March 2022) - Nevin, Suzanne M.; Wakefield, Claire E.; Le Marne, Fleur; Beavis, Erin; Macintosh, Rebecca; Sachdev, Rani; Bye, Ann; Palmer, Elizabeth E.; Nunn, Kenneth
Abstract: Developmental and epileptic encephalopathies (DEEs) are chronic and life-threatening conditions, frequently with a genetic basis and infantile-onset. Caregivers often experience enduring distress adapting to their child's diagnosis and report a deficit of accessible psychological supports. We aimed to pilot a novel, empirically-driven suite of audio-visual positive psychology resources tailored for caregivers of children with a DEE, called 'Finding a Way'. Methods: We recruited caregivers through two paediatric hospital databases, and we also shared an invitation to the online questionnaire via genetic epilepsy advocacy organisations. The online questionnaire included a combination of validated, purpose-designed, and open-ended questions to assess the acceptability, relevance, and emotional impact of the resources among caregivers. Results: 167 caregivers from 18 countries reviewed the resources, with 56 caregivers completing over 85% of the evaluation. Caregivers rated the resources as highly acceptable and relevant to their experiences. In both the quantitative and qualitative data, caregivers reported that the resources normalised their emotional experiences and provided helpful suggestions about managing their personal relationships, seeking support and accepting help from others. Frequently reported emotional responses after viewing the resources included feeling "comforted", "hopeful", "connected" and "reassured". Suggestions for improvement included, expanding the suite of resources and embedding the resources with links to specialised psychological services. Conclusion: 'Finding a Way' is a novel codesigned suite of audio-visual positive psychology resources tailored for caregivers of children with DEEs. Our results suggest that 'Finding a Way' is acceptable to caregivers and may contribute towards enhanced emotional adaptation and coping. Highlights: Caregivers of children with genetic DEEs exhibit high rates of poor mental health outcomes including depression, anxiety and chronic traumatic stress disorder. Psychological resources designed to support caregiver psychological wellbeing are sparse due to the rarity of individual DEE diagnoses. An exploration of the acceptability of codesigned psychological resources is necessary to assess whether they provide any benefit and to identify areas for improvement. Positive psychology resources may improve caregiver psychological adjustment to their child's diagnosis and their caregiving role.